2006
DOI: 10.2190/b176-7341-45u7-n6h4
|View full text |Cite
|
Sign up to set email alerts
|

African-American Retention within a Community College: Differences in Orientation Course Enrollment

Abstract: Investigation of orientation programs and African-American student retention, particularly within the community college sector, has long been neglected. This study specifically investigates the differences between an orientation course and student retention measures, for African-American student retention. Chi-square analysis revealed significant differences for orientation course enrollment, student retention, and persistence.Retaining minority students within higher education, specifically for community coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…However, the finding of this study seems to support the study by Derby and Watson (2006) that found chance differences between African American student participation in an orientation course and degree completion. The second surprising result of this study concerned Hispanic student participation within the orientation course and degree completion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the finding of this study seems to support the study by Derby and Watson (2006) that found chance differences between African American student participation in an orientation course and degree completion. The second surprising result of this study concerned Hispanic student participation within the orientation course and degree completion.…”
Section: Discussionsupporting
confidence: 83%
“…Similar associative relationships were revealed for both African American and Hispanic orientation course participants and degree completion in a different study (Derby, 2006). Despite these findings, Derby and Watson (2006) did not find an relationship between orientation course participation and African American degree completion, but rather found associative relationships between such participation and student retention and persistence. These studies however, cannot speak to the potentially predictive relationship between both orientation course participation and or orientation participation by minority groups and degree completion.…”
contrasting
confidence: 66%
“…Student success courses, which through the years have been alternately identified as orientation courses and freshman year or success seminars, are characterized as programs aimed at assisting new entering students to transition to college (Cook, 1996). Programmatic goals are typically centered on providing information and assistance to students in the areas of study skills, learning styles, strategies for college success, educational and career planning and development, introduction to campus facilities, resources, services, and personal development such as health and=or well-being strategies (e.g., Derby, 2007;Derby & Watson, 2006;Walls, 1996).…”
Section: Student Success Coursesmentioning
confidence: 99%
“…The impact or relationship between student success courses and course completion is even less clear as findings from two studies indicated a positive relationship (i.e., Derby & Watson, 2006;Stovall, 1999) and two did not (i.e., Grunder & Hellmich, 1996;Walls, 1996). Similarly, while some studies have found student success courses to be positively related to graduation or earning a degree (i.e., Derby & Smith, 2004;Raymond & Napoli, 1998;Stovall, 1999;Zimmerman, 2000), findings by Derby andWatson (2005, 2006), which focused on Hispanic and African American students, did not identify a significant relationship.…”
Section: Student Success Coursesmentioning
confidence: 99%
“…This is particularly the case in the current study, as participants were initially part of the Opening Doors study, a randomized controlled trial of an intervention with such a goal. Previous research has provided support that similar educational interventions, including orientation programs, specialized coursework, and extra advising, significantly increase community college retention (e.g., Berkovitz & O’Quin, 2006–2007; Derby & Watson, 2006; Driskoll, 2007; Pascarella, Terenzini, & Wolfe, 1986; Tinto, 1997). The Opening Doors program might also have alleviated financial concerns, as it provided students with a $1,000 stipend per semester.…”
Section: Introductionmentioning
confidence: 99%